1983
DOI: 10.1177/106002808301700618
|View full text |Cite
|
Sign up to set email alerts
|

Use of Anticholinergics in the Nursing Home: An Empirical Study and Review

Abstract: The Medicare Utilization Review Committee conducted a survey to determine the use of drugs with anticholinergic effects in confused elderly nursing home patients. Twenty-nine patients (34.5 percent) were receiving anticholinergic drugs, predominantly from the antidepressant and antipsychotic class. Thioridazine (Mellaril) was the most frequently used antipsychotic. No patients received higher than the equivalent recommended daily dose of atropine when calculated in terms of relative anticholinergic potency. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
1
10
1
Order By: Relevance
“…The results from other studies vary, however. Seifert et al 7 reported that 34.5% of nursing home patients were receiving anticholinergic drugs, which is similar to our result. Other investigators have not presented the overall use of this group of medicines.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results from other studies vary, however. Seifert et al 7 reported that 34.5% of nursing home patients were receiving anticholinergic drugs, which is similar to our result. Other investigators have not presented the overall use of this group of medicines.…”
Section: Discussionsupporting
confidence: 92%
“…The use of neuroleptics, especially in institutions, was more common. Neuroleptic use in nursing homes was 33%, which is higher than the prevalences between 17 and 24% reported in previous studies 1,3,7 . In institutions in general, neuroleptic use was more than three times higher than that reported by Skoog et al in their study of 85‐year‐old subjects in Gothenburg 8 .…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Over 600 plants, chemicals, and pharmaceutical products have anticholinergic properties 7 . Drugs with anticholinergic effects are frequently used in the elderly 8–10 . We have found that 45% of elderly patients in a chronic care institution were receiving at least one drug with anticholinergic side effects 11 .…”
Section: Discussionmentioning
confidence: 99%
“…[1–4] Despite known potential adverse consequences, anticholinergic use is still common in older adults, both in long-term care and community settings. Older studies have reported anticholinergic medication use prevalence of 34% to 59% in skilled nursing facility residents [5, 6] and 23% to 50% in older adults in ambulatory care. [68]…”
Section: Introductionmentioning
confidence: 99%